Development of creativity for increasing the stress-resistance of schoolchildren (Journal of Educational Sciences, 2018)
The article raises the actual topic of schoolchildren`s stress resistance development of 9 classes using creative methods of teaching. The notions of «stress-resistance», «creativity», the theory of the stress-stability of G. Selje, T. Koks and others are considered. Stress is expressed in the increased tension of a person, his mental, physical and spiritual forces. Based on the general scientific foundations for the development of stress resistance and creativity, we have compiled a model and an algorithm for getting out of stress. The model includes goals and objectives, the content of development of stressresistance and creativity, an algorithm and a program for developing creativity to overcome stress, the result. The algorithm includes three components: (1) the emergence of a stressful situation, (2) a person’s awareness of the stress situation and the definition of his parameters, (3) the use of creative methods to overcome stress. Based on the model and algorithm, a training program was developed to improve the stress-resistance and creativity of schoolchildren. For the approbation of the algorithm, an experimental and pedagogical work was carried out on the basis of school # 55 in Almaty. In the experimental and pedagogical study, 50 pupils of two 9th grades have participated. Tests which were used at the diagnostic stage: J. Bruner’s creativity level; a test for self-assessment of the stress-resistance of the personalityby NV Kirsheva, NV Ryabchikova; Methodology «Scale of psychological stress PSM-25» Lemur-Tesye- Fillion. At the first stage it is established that 64% of students have a low level of creativity, an average of 24%, and a high level of 12%. After the formative stage, it was found that the percentage of children with a high level of creativity was raised to 20% among respondents , and an average level is up to 48%. 32% of students have a low level of creativity. The technique «Psychological Stress Scale PSM-25» of Lemur-Tesye-Fillion was conducted. During the experimental group test, we obtained the following results: 16% of respondents have a high level of stress, 44% of respondents have an average level of stress, and 40% of respondents have a low level of stress.Key words: creativity, stress, stress resistance, creative teaching methods, school.